Characterization of a pESI-like plasmid and analysis of multidrug-resistant Salmonella enterica Infantis isolates in England and Wales. Issue 10 (14th October 2021) - Lee, Winnie W. Y.; Mattock, Jennifer; Greig, David R.; Langridge, Gemma C.; Baker, David; Bloomfield, Samuel; Mather, Alison E.; Wain, John R.; Edwards, Andrew M.; Hartman, Hassan; Dallman, Timothy J.; Chattaway, Marie A.; et al.
Abstract : Salmonella enterica serovar Infantis is the fifth most common Salmonella serovar isolated in England and Wales. Epidemiological, genotyping and antimicrobial-resistance data for S . enterica Infantis isolates were used to analyse English and Welsh demographics over a 5 year period. Travel cases associated with S . enterica Infantis were mainly from Asia, followed by cases from Europe and North America. Since 2000, increasing numbers of S . enterica Infantis had multidrug resistance determinants harboured on a large plasmid termed 'plasmid of emerging S . enterica Infantis' (pESI). Between 2013 and 2018, 42 S . enterica Infantis isolates were isolated from humans and food that harboured resistance determinants to multiple antimicrobial classes present on a pESI-like plasmid, including extended-spectrum β-lactamases (ESBLs; bla CTX-M-65 ). Nanopore sequencing of an ESBL-producing human S . enterica Infantis isolate indicated the presence of two regions on an IncFIB pESI-like plasmid harbouring multiple resistance genes. Phylogenetic analysis of the English and Welsh S . enterica Infantis population indicated that the majority of multidrug-resistant isolates harbouring the pESI-like plasmid belonged to a single clade maintained within the population. The bla CTX-M-65 ESBL isolates first isolated in 2013 comprise a lineage within this clade, which was mainly associated with South America. Our data, therefore, show the emergence of a stable resistant clone that has been in circulation for some time in the human population in England and Wales, highlighting the necessity of monitoring resistance in this serovar.